An exploratory study of organizational values in jails - Aquino, Karl (International journal of value-based management, 1995)
This research inductively identifies dimensions of organizational values which guide the operation and management of jails. A set of twenty-three value items were collected from jail administrators. Officers in five facilities were then asked to indicate the extent to which their administrators emphasized each value through their actions, statements, and policies. A principal components analysis showed that a subset of values could be represented by two underlying dimensions. A second survey of jail administrators showed that four values were consistently ranked as being of high priority relative to others. Implications for jail management are discussed and future research directions are offered.